Challenges and Opportunities in Smart Contract Development on the Ethereum Virtual Machine: A Systematic Literature Review - Velasco, Gislainy Crisostomo; Vaz, Noeli Antonia Pimentel; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2023: Anais do VI Workshop em Blockchain: Teoria, Tecnologias e Aplicações, 2023)
The development of smart contracts presents significant challenges compared to traditional software development, such as the immutability of the blockchain. This paper presents a systematic literature review (SLR) that aims to understand the limitations and challenges faced by smart contract developers on the Ethereum Virtual Machine (EVM). Among the main challenges identified are language restrictions, infrastructure limitations, and the lack of sufficient information on interface patterns and implementation specifications. Existing proposals are difficult to understand, with complex formal verifications that require advanced technical knowledge. Additionally, the scarcity of accessible educational resources for training new smart contract developers represents a major challenge to be overcome. In this regard, the SLR seeks to identify opportunities for improvement and innovation in the field, as well as validation and evaluation strategies to make the smart contract development process more efficient and secure.